ANALISA LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA PADA PT SATUNOL MIKRO SISTEM JAKARTA - Hamizar Hamizar; Muhammad Iqbal (POLITEKNIK LP3I JAKARTA, 2019)
This study aims to determine the condition of financial statements PT Satunol Mikro Sistem Jakarta, find out the performance of PT Satunol Mikro Sistem Jakarta in 2015, 2016, and 2017 in terms of Liquidity, Activity and Profitability ratios by focusing on the financial statements of PT Satunol Mikro Jakarta System which consists of Financial Position Report and Income Statement period 2015, 2016, and 2017. The method used by the writer is descriptive analysis method. Data collection techniques used by the author are observation and literature study with horizontal financial statement comparison analysis techniques, liquidity ratios, activity ratios and profitability ratios. The results obtained that the financial situation of PT Satunol Mikro Sistem Jakarta is fluctuating. Based on the calculation of the liquidity ratio, PT Satunol Mikro Sistem Jakarta is in a liquid state because the company is able to pay off all its short-term debt. Based on the calculation of the activity ratio, PT Satunol Micro Systems Jakarta has not been effective in carrying out its daily activities and the company has not efficiently reduced its operating costs. Based on the calculation of profitability ratios, PT Satunol Mikro Sistem Jakarta has not been able to increase its profits and has a low ratio level and far from the industry average. That is, even though the company made a profit, the company did not get the profit as expected, or it was not above the average industry ratioKeywords: Financial Statement Analysis, Liquidity Ratio, Activity Ratio, Profitability Ratio.